2016
DOI: 10.1177/0022146516671568
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Effects of Growing Up in Separate and Unequal Neighborhoods on Racial Disparities in Self-rated Health in Early Adulthood

Abstract: Evidence suggests that living in a socioeconomically deprived neighborhood is associated with worse health. Yet most research relies on cross-sectional data, which implicitly ignore variation in longer-term exposure that may be more consequential for health. Using data from the 1970 to 2011 waves of the Panel Study of Income Dynamics merged with census data on respondents’ neighborhoods (N = 1,757), this study estimates a marginal structural model with inverse probability of treatment and censoring weights to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 95 publications
3
13
0
Order By: Relevance
“…Although no study to date has examined long‐term trajectories of neighborhood SES in relation to CRC, several studies have examined their associations with other health outcomes. Kravitz‐Wirtz reported that growing up in neighborhoods characterized by long‐term low SES was associated with worse self‐rated health . Margerison‐Zilko and colleagues reported that long‐term high poverty in the neighborhood was associated with higher odds of preterm birth .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no study to date has examined long‐term trajectories of neighborhood SES in relation to CRC, several studies have examined their associations with other health outcomes. Kravitz‐Wirtz reported that growing up in neighborhoods characterized by long‐term low SES was associated with worse self‐rated health . Margerison‐Zilko and colleagues reported that long‐term high poverty in the neighborhood was associated with higher odds of preterm birth .…”
Section: Discussionmentioning
confidence: 99%
“…Kravitz-Wirtz reported that growing up in neighborhoods characterized by long-term low SES was associated with worse self-rated health. 25 Margerison-Zilko and colleagues reported that long-term high poverty in the neighborhood was associated with higher odds of preterm birth. 26 In addition, Sheehan et al observed that individuals living in census tracts with long-term high poverty had higher odds of being obese and had higher BMI values than those who lived in census tracts with long-term low poverty.…”
Section: Discussionmentioning
confidence: 99%
“…SRH is also used for cross-country comparisons [23,24,25,26,27,28,29] and policy development [30,31,32,33]. It is used as a reflection of health disparities and inequality [34,35,36,37]. SRH is also used to track the subjective health of individuals with index psychiatric or medical conditions [38].…”
Section: Introductionmentioning
confidence: 99%
“…This is one of a number of methodological challenges that has led to an impasse in progress in neighbourhood effects research (van Ham and Manley, 2012). Examples of empirical work where it is assumed individuals will be affected by their neighbourhood more (or less) at certain periods during the life course are rare (Kravitz-Wirtz, 2016a;Lekkas et al, 2017;Murray et al, 2012;Pearce, 2018). The potential of sensitive neighbourhood effect periods is an important hypothesis to test, not least because people move between neighbourhoods and neighbourhoods improve and decline, and therefore a single point in time measurement may misinterpret any neighbourhood effect (Murray et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We also add to the existing literature by using data on two separate cohorts that enables us to explore whether sensitive periods are specific to one generation or can be indicative of a wider trend. We test multiple dimensions of health, including general (Dundas et al, 2014;Johnson et al, 2012;Kravitz-Wirtz, 2016a), physical (Clarke et al, 2014;Kravitz-Wirtz, 2016b;Murray et al, 2013;Ruel et al, 2010) and mental health (Clarke et al, 2015;Walsemann et al, 2017) to explore our wider concept of wellbeing. Each outcome used in this study has been shown in earlier literature to be affected by neighbourhood context.…”
Section: Introductionmentioning
confidence: 99%